Employed relative careers in Sweden 1993 - Employed relative carers in Sweden 1993 - Furåker, Bengt; Sand, Ann-Britt (University of Gothenburg, 2001)
In Sweden the municipalities have the responsibility to provide the elderly, ill and disabled with the assistance they need to make home living possible. Still, most caring take place in the family and is performed by relatives. Sometimes a relative carer can be employed and paid by the municipality to perform the help. The aim of this study is to explore the situation of employed family careers.

Purpose:

The aim of this study is to explore the situation of employed family careers.

I Sverige ansvarar kommunerna för att ge äldre, sjuka och handikappade det stöd som de behöver för att kunna göra det möjligt att bo i sitt eget hem. Mycket omvårdnad utförs dock fortfarande av anhöriga. I vissa fall kan en anhörig bli anställd och få lön av kommunen då de tar hand om en släkting. Syftet med den här studien är att undersöka situationen för anställda anhöriga.

Syfte:

Syftet med den här studien är att undersöka situationen för anställda anhöriga.
Anhörigvård 1993
Keywords: ethics; etik; employment; anställning; care of the elderly; äldreomsorg; health; hälsa; family life; familjeliv; diseases; sjukdomar; care of dependants; anhörigvård; gender; genus; home help; hemtjänst; social responsibility; socialt ansvar; physical mobility; fysisk rörlighet; care of the disabled; handikappomsorg; home-based work; arbete hemifrån; responsibility; ansvar; conditions of employment; anställningsvillkor; care in the community; hemvården; families; familjer; social welfare philosophy; social välfärdsfilosofi; welfare policy; social- och välfärdspolitik; disabilities; funktionsnedsättningar; Working conditions; Arbetsförhållanden; Elderly; Äldre; Social welfare systems/structures; Sociala välfärdssystem/-strukturer; Specific social services: use and availability; Specifika sociala tjänster: användning och tillgänglighet; Social Sciences; Samhällsvetenskap; Sociology; Sociologi